Open Power System Data – Frictionless data for electricity system modelling. (15th February 2019) - Wiese, Frauke; Schlecht, Ingmar; Bunke, Wolf-Dieter; Gerbaulet, Clemens; Hirth, Lion; Jahn, Martin; Kunz, Friedrich; Lorenz, Casimir; Mühlenpfordt, Jonathan; Reimann, Juliane; Schill, Wolf-Peter
Graphical abstract: Highlights: Quality of electricity system modelling heavily relies on input data. Centralised and open provision of input data increases both transparency and efficiency. A lot of data is publicly available, but often dispersed and tedious to process. The Open Power System Data platform aims to overcome these challenges. Abstract: The quality of electricity system modelling heavily depends on the input data used. Although a lot of data is publicly available, it is often dispersed, tedious to process and partly contains errors. We argue that a central provision of input data for modelling has the character of a public good: it reduces overall societal costs for quantitative energy research as redundant work is avoided, and it improves transparency and reproducibility in electricity system modelling. This paper describes the Open Power System Data platform that aims at realising the efficiency and quality gains of centralised data provision by collecting, checking, processing, aggregating, documenting and publishing data required by most modellers. We conclude that the platform can provide substantial benefits to energy system analysis by raising efficiency of data pre-processing, providing a method for making data pre-processing for energy system modelling traceable, flexible and reproducible and improving the quality of original data published by data providers.